Meningkatkan Kolaborasi Masyarakat dalam Membangun Desa Jambearum Bebas Stunting melalui Optimalisasi Manajemen Sumber Daya Manusia - Fawaid, Achmad; Hibatulah, Hafidz Denia; Indriani, Mita; Norbaity, Tiara Wahyu; Agustina, Rizki Ika; Nugraha, Widya Agung; Huzaimah, Siti; Siahaan, Nadya Natasha; Ramadhan, Alvian Madafiqiya; Sari, Yessy Kusuma; Wardani, Rendi Ali; Safitri, Mutiara Dewi; Aprilia, Diah Putri; Sufi, Queen Nurul; Putri, Tania Aprilliani (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This service program aims to increase community collaboration in building Jambearum Village to be stunting free through optimizing human resource management. The results of outreach activities regarding stunting show that the community feels helped and understands the importance of preventing stunting. Through the ABCD (Asset-Based Community Development) method, we convey information and empower the community to apply knowledge regarding stunting prevention. With strong collaboration, we hope that this effort can reduce the stunting rate in Sumber Kokap Timur and Sumber Kokap Barat Hamlets, Jambearum Village. The success of this program is measured by participation and changes in community behavior in implementing the stunting prevention measures that have been socialized.